1984
DOI: 10.1128/aac.25.4.438
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone pharmacokinetics in patients with various degrees of renal impairment

Abstract: The effects of renal impairment on the pharmacokinetics of ceftriaxone in humans were examined after intravenous infusion of a 1-g dose over 15 min to 30 renally impaired patients. The study included 12 dialysis patients and 18 patients with severe, moderate, or mild renal impairment. Plasma and, where appropriate, urine and dialysate samples were collected at predetermined times and analyzed for ceftriaxone by highpressure liquid chromatography. The elimination half-life (group mean ranged from 11.7 to 17.3 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1
7

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 13 publications
2
58
1
7
Order By: Relevance
“…In ESRD patients the T ½ of the drug has been reported to be much longer but variable, ranging from 11.7 to 17.3 h [19,23,24]. It has been shown that ceftriaxone is not removed to any significant extent from plasma by hemodialysis [19,20]. Thus, in these patients ceftriaxone is a truly once-a-day antibiotic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ESRD patients the T ½ of the drug has been reported to be much longer but variable, ranging from 11.7 to 17.3 h [19,23,24]. It has been shown that ceftriaxone is not removed to any significant extent from plasma by hemodialysis [19,20]. Thus, in these patients ceftriaxone is a truly once-a-day antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Its major route of elimination is via the kidney (41-60%), wherein it is disposed by glomerular filtration without any significant renal tubular secretion [15,16,22]; the remainder is excreted in the bile [15,16]. In ESRD patients the T ½ of the drug has been reported to be much longer but variable, ranging from 11.7 to 17.3 h [19,23,24]. It has been shown that ceftriaxone is not removed to any significant extent from plasma by hemodialysis [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of cloxacillin, [11] oxacillin, [12] pefloxacin, [13] ceftriaxone, [14] and fusidic acid [15] should not be influenced by RI. In renal impairment (including patients with end-stage renal failure), these drugs are reported to be safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftriaxone is a third-generation ce phalosporin (2-amino-thiazolylmethoxyimino cephalosporin) that, because of its prolonged elimination half-life, can be ad ministered safely in a once-a-day dosage schedule [2,6,7], This characteristic is an advantage over similar cephalosporins such as cefotaxime, cefoperazone and latamoxef. They all have an excellent antib acterial activity against many pathogens previously considered resistant to the firstand second-generation cephalosporins [9], The pharmacokinetic parameters of cefo taxime, cefoperazone and latamoxef do not differ substantially from those of the older cephalosporins and their elimina tion half-lives ranging from 1.2 to 2.4 h in man are shorter than the 8 h value ob served for ceftriaxone [2,6,16].…”
mentioning
confidence: 99%